(untitled) (Revista de Artes Marciales Asiáticas, 2021)
Strength-endurance is one of the trainable physical capacities that could determine the success in some combat sports and its inclusion is obligatory in the training periodization of high-level athletes. In striking combat sports, such as boxing and taekwondo, it seems likely that increases in dynamic strength-endurance improve the ability to execute combat movements repeatedly. On the other hand, grapplers need to develop high levels of strength-endurance because during the match much time is spent in grip dispute and the success in this phase may determine the possibility to execute scoring techniques. Furthermore, in mixed combat sports, where a combination of striking and grappling are required, athletes needs to have the capacity to maintain dynamic or static muscular actions during prolonged periods during the match, and the strength-endurance is one key element. Therefore, this chapter presents the strength-endurance requirements during the match, the specific tests for its evaluation, scientific evidence of longitudinal studies on the development of strength-endurance in combat sports athletes and the methods for its development.